ANALISIS FORENSIK CITRA DI PLATFORM X MENGGUNAKAN METODE DIGITAL FORENSIC RESEARCH WORKSHOP (DFRWS) - Wicaksono Yuli Sulistyo; Septia Ayu Pratiwi; Muhammad Haedar Zhafran Hidayatullah (IDEALIS : InDonEsiA journaL Information System, 2025)
One of the negative impacts observed is the uncontrolled behavior of individuals in using personal applications, which has the potential to lead to cybercrimes. Common cases of cybercrime on social media involve posting photos for bullying purposes, spreading false information, fraud, and defamation. Photos can be easily altered or edited, enabling the manipulation of information that could be exploited for malicious activities. Nowadays, the ease of uploading photos and the difficulty in detecting their authenticity are key factors underlying this study, which aims to detect digital photo forgery in the platform X. The study adopts the Digital Forensic Research Workshop (DFRWS) framework to identify instances of digital photo forgery. The key stages implemented in this research include identification, preservation, collection, examination, analysis, and presentation. The findings revealed pixel alterations in the smartphone object area and other regions, indicating manipulation and making the image appear different from the original. Additionally, using FotoForensic, metadata from the photos was successfully retrieved, revealing that the second photo had been edited and previously modified using Adobe Photoshop CC 2017. Furthermore, analysis with ForensicallyBeta identified pixel discrepancies in several parts of the image, showing additional noise, which confirmed that the photo had been edited in specific areas, thus indicating its lack of authenticity.